Lipoatrophic linear morphea in a 5-year-old girl: A novel variant? - Vibhu Mendiratta; Mansi Bansal; Shivangi Rana; Kiran Agarwal (Wolters Kluwer Medknow Publications, 2021)
Introduction: Morphea profunda or subcutaneous morphea is a variant of morphea in which inflammation and sclerosis found in deep dermis, subcutaneous tissue, fascia or muscle. Case report: We are report an atypical case of subcutaneous morphea in five year-old girl, presenting with atrophy of subcutaneous fat over the left lower limb in a liner pattern, closely mimicking linear lipoatrophy. Discussion: Early intervention in such cases can halt progression of the disease.